Pelatihan Penentuan "Expired date" Produk Minuman Instan Berbahan Tanaman Obat Pada Kelompok Usaha di Kecamatan Insana Barat - Satmalawati, MM Endah; Nino, Jefrianus; Banunaek, Zfar (Jurnal Pengabdi, 2023)
The processing of rhizome plants such as ginger, turmeric, white turmeric and ginger into instant products carried out by three (3) Joint Business Groups (KUB) in the West Insana District area has long been known and has been marketed widely both in TTU Regency and outside the area. (Belu, Malacca and Flores). Products that have been accepted by the public must be balanced with the quality of the packaging, where one of the quality attributes is the expiry date information. Until now, the inclusion of expiration dates on packaging is still based on assumptions/conjectures and not based on scientific studies with accurate calculation methods, so it cannot fully guarantee consumer safety for the products they consume. This community service activity uses lecture and practical methods which are divided into 2 stages, namely stage 1: socializing the importance of including Expired date information on packaging as a form of producer responsibility and this activity is carried out in 4 KUBs in the West Insana District area (KUB Tnoumat II, KUB Lestari, KUB Prima Mandiri and KUB Melati) at the location of one of the KUBs, namely Usapinonot Village, and continued with stage 2 of training in determining accurate product quality in the form of practices carried out at the Laboratory of the Faculty of Agriculture, University of Timor. The result of this activity is an increase in the understanding and knowledge of the medicinal plant rhizome processing community in the West Insana District area regarding determining product thickness accurately and more responsibly to improve product quality and the level of consumer confidence, expand the market and contribute to advancing the regional economy